Amazing Animal Hide and Seek - Rowe, John (Hutchinson, 2003)
First, kids must find the Cat who is hiding in a field. His colors blend in with the many other details in this vividly colored illustration, so toddlers will have to look very carefully. Once theya've found Cat, they can turn to the next page and seek out one more animal friend in hiding. Finally, at the storya's end, all the animals have been found and have returned home to rest.
Keywords: Juvenile Fiction Animals